Reimagining Tourism: A Creative Model for Destinations Facing Negative Impacts - Hernández Matorel, Moisés David (Eco-Tourism and Sustainable Development, 2025)
Tourism has been recognized as a significant driver of economic growth across the globe. Nonetheless, numerous destinations are increasingly facing negative consequences, including the erosion of cultural heritage, authenticity and the emergence of environmental, social, and economic challenges that disproportionately affect local communities. In response to these issues, this paper proposes a theoretical model that positions creative tourism as an alternative to mitigate such adverse effects. By promoting creative experiences that engage both tourists and local stakeholders, the model encourages more inclusive, culturally grounded, and sustainable forms of tourism development. The study employs a qualitative methodology based on a theoretical modeling approach from the social sciences. This process includes a systematic overview of literature and analytical categories to address identified social problems. Data triangulation was used by integrating information from bibliographic sources, institutional reports, and ethnographic fieldwork used in diverse tourism destinations. Findings emphasize the relevance of placing tourist experiences at the center of destination planning and management, highlighting the interaction between experience design, cultural authenticity, and local participation. This research underscores how creative tourism, when thoughtfully implemented, has the potential to generate meaningful, sustainable impacts that benefit both visitors and host communities. Furthermore, the proposed model offers practical and conceptual tools for rethinking tourism practices through a more sustainable, culturally rich, and conscious lens.